Pengembangan Kemampuan Berbahasa Melalui Metode Cerita Dengan Membacakan Buku Cerita Bermedia Gambar Pada Anak Pra Sekolah - Arifal Aris; Andri Tri Kusumaningrum (Jurnal Keperawatan Muhammadiyah, 2017)
This research is motivated by learning for develop of language ability on preschoolers. Based on preliminary survey conducted at kindergarten Aisyiah Bustanul Athfal (ABA) II Made Lamongan still get the delay of child language development which can affect the learning process. One of the interventions to develop children’s speaking skills need to be done in the right way,   one of them by using picture story method.Research design using pra-experimental design with one-group Pre-Post Test Design. Population of 47 using simple random sampling. Independen variabel of storytelling method, dependent  variable  of  child  language development.  Technique of  collecting data using Denver Development Screning Test II(DDST) sheets. Data was tabulated and analyzed using wilcoxon test with significant level α<0.05.The result showed that the language development of preschoolers 4-6 years at kindergarten ABA II Made before intervention 29 children (69%), after done picture meth result 40 childre (95,2 %). Result wilcoxcon test, with a value of p = 0.001 where p <0.05, then rejected or capted, it means there is influence of storytelling method on language develop in kindergarten ABA II Made sub district Lamongan distric Lamongan.The need for the development of teaching activities in kindergarten by adding a storytelling method  to  stimulate  the  language  development  of  children  so  as  to  provide  a  new  learning experience for children.